2023
DOI: 10.1007/s10570-023-05285-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonwoven fabrics developed from agriculture and industrial waste for acoustic and thermal applications

Abstract: Numerous researchers in the field of noise control and acoustics have found success in using biomaterials to create a porous sound absorber that is both effective and environmentally friendly. This paper discusses the utilization of fibers extracted from the waste from coffee husk (CH) and waste from the cotton (CO) spinning industry to be an alternative to synthetic-based acoustic materials. The study was conducted within the range of 50–6300 (Hz) frequency. Five well-known mathematical prediction models, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In recent studies, researchers have shown that chitosan modified cellulosic non-woven fabric has superior color removal capabilities for Reactive Red 198 [147]. Additionally, these non-woven fabrics have shown great potential as materials for dye removal in the future [148,149].…”
Section: Sustainable Wastewater Treatment For the Remediation 41 Bioa...mentioning
confidence: 99%
“…In recent studies, researchers have shown that chitosan modified cellulosic non-woven fabric has superior color removal capabilities for Reactive Red 198 [147]. Additionally, these non-woven fabrics have shown great potential as materials for dye removal in the future [148,149].…”
Section: Sustainable Wastewater Treatment For the Remediation 41 Bioa...mentioning
confidence: 99%
“…Moreover, recycled polypropylene and polyester absorb sound at mid-range frequencies more efficiently owing to their inhomogeneity and micro voids [15]. However, it was found that acoustic performance is affected by the fiber type, fineness, density, bonding methods, airflow resistivity, and porosity of nonwovens [16,17]. Increasing the proportion of fibers with smaller diameters in a given layer (which decreases the air permeability) or increasing the thickness of a layer containing a given distribution of fiber diameters improves the sound absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Non-woven needle-punched materials (used for gas and liquid filtration [1][2][3][4], heat [4][5][6][7][8] and sound insulation [7][8][9][10][11], and road and hydraulic engineering construction [11][12][13][14], etc. ), must have high permeability and sufficient mechanical properties for practical uses that depend on the fabric's porosity [15].…”
Section: Introductionmentioning
confidence: 99%